1991
DOI: 10.1161/01.str.22.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Brain polyphosphoinositide metabolism during focal ischemia in rat cortex.

Abstract: Using a rat model of stroke, we examined the effects of focal cerebral ischemia on the metabolism of polyphosphoinositides by injecting "Pi into both the left and right cortices. After equilibration of the label for 2-3 hours, ischemia induced a significant decrease (p<0.001) in the concentrations of labeled phosphatidyl 4,5-bisphosphates (66-78%) and phosphatidylinositol 4-phosphate (64-67%) in the right middle cerebral artery cortex of four rats. The phospholipid labeling pattern in the left middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…These findings are similar to those observed with hypoxic ischemia in which intracellular IP 3 levels increased with 30-60 seconds of insult (12,14,31). The mechanism underlying the response to cyanide is not clear.…”
Section: ‫ם2‬supporting
confidence: 82%
See 1 more Smart Citation
“…These findings are similar to those observed with hypoxic ischemia in which intracellular IP 3 levels increased with 30-60 seconds of insult (12,14,31). The mechanism underlying the response to cyanide is not clear.…”
Section: ‫ם2‬supporting
confidence: 82%
“…Hypoxia/ischemia activates polyphosphoinositide hydrolysis leading to formation of inositol phosphates (12)(13)(14). Phospholipase C (PLC) activation is thought to be responsible for the hypoxia-ischemiainduced polyphosphoinositide hydrolysis (15,16).…”
Section: ‫ם2‬mentioning
confidence: 99%
“…Our results regarding the relationship b e t w e e n L C B F and histological d a m a g e during the first 3 hours after M C A O began m a y support the previous observation that the striatum is m o r e vulnerable than the cortex [21,22,33]. In the assessment of the vulnerability of the neuronal cell itself, start of MCAO may indicate increase in the rate of hydrolysis of phospho-inositides into diacylglycerol and IP3 during and after ischaemia, and may also enhance PKC activity [10,19,26,41]. Tanaka et al [35] also indicated that the unilateral common carotid artery occlusion model of gerbil rats increased significantly the PDBu binding activity in the severe ischaemic area, 2 hours after initiation of occlusion.…”
Section: Histological Examinationsupporting
confidence: 79%
“…As a result of the similarity in acyl group composition between DG and phosphatidylinositol (PI), a metabolic relationship between these two types of lipids has been suggested (Keough et al, 1972). More recently, studies have provided evidence for stimulated hydrolysis of poly-phosphoinositides (poly-PI) but not PI resulting from cerebral ischemia Huang and Sun, 1986;Yoshida et al, 1986;Abe et al, 1987;Sun, 1989;Sun et al, 1988Sun et al, , 1990Lin et al, 1991). These studies further demonstrated the involvement of the bifurcating signaling system with the release of two and DG for activation of protein kinase C (Berridge, 1987).…”
Section: Is ^1mentioning
confidence: 99%